Sistematización de procesos gerenciales de Pyme´S A través de la auditoría informática. - Calle Loaiza, Adriana Karolina (My University, 2019)
The relevant documentation relates the main computer pretexts aimed at optimizing, systematizing and integrating digital mechanisms in accounting processes, in order to improve managerial activities and induce a favorable cash flow; as well as assist in making decisions, monetary management and utility when evaluating the performance of the company. Abductive methods, content analysis and bibliographic research are applied when acquiring, processing and interpreting information in order to successfully combine managerial models that operate through virtual media and pretend to describe their relevance within the scope of business administration. The results list the commercial software, techniques, protocols and inferences that are used today, businessmen to adjust their income / expenses, what measures they exercise to manage their expenses and investments, how digital systems optimize this work in a reliable way and safe.
La documentación pertinente relata los principales pretextos informáticos orientados a optimizar, sistematizar e integrar mecanismos digitales a los procesos contables, con el objeto de mejorar las actividades gerenciales e inducir un flujo de caja favorable; así como asistir en la toma de decisiones, gestión monetaria y utilidad al evaluar el desempeño de la empresa. Se aplica los métodos abductivo, análisis de contenidos e investigación bibliográfica al adquirir, tratar e interpretar información con la finalidad de conjugar exitosamente los modelos gerenciales que operan a través de medios virtuales y pretender describir su relevancia dentro del ámbito de la administración de empresas. En los resultados se enlista los softwares comerciales, técnicas, protocolos e inferencias que utilizan hoy en día, los empresarios al cuadrar sus ingresos/egresos, que medidas ejercen para administrar sus gastos e inversiones, cómo los sistemas digitales optimizan esta labor en forma confiable y segura.
Keywords: AUDITORIA INFORMÁTICA; PROCESOS CONTABLES; PYMES; SISTEMAS